1975
DOI: 10.1093/geronj/30.6.688
|View full text |Cite
|
Sign up to set email alerts
|

Modernization, Modernity, and Perceptions of Aging: A Cross-Cultural Study

Abstract: Data from a comparative study of 5,450 young males in six developing nations were used to investigate the association between modernization or modernity and negative attitudes toward aging. The findings question the frequent assertion that "modernity" (the exposure of individuals in developing nations to industrial technology and urban social experience) results in negative perceptions of aging and diminished value attributed to the aged. The data do provide support for the hypothesis that "modernization" (soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 0 publications
2
21
0
1
Order By: Relevance
“…For example, the usefulness of older adults eroded with the shift from an agricultural to a more industrial society [39]. The theory has been used to understand negative attitudes toward aging [41], as well as family relationships [42] and family caregiving dynamics [43]. Achenbaum and Sterns [44] note there needs to be more agreement regarding when modernization first began as well as classifying stages within modernization.…”
Section: Psychosocial Theoriesmentioning
confidence: 99%
“…For example, the usefulness of older adults eroded with the shift from an agricultural to a more industrial society [39]. The theory has been used to understand negative attitudes toward aging [41], as well as family relationships [42] and family caregiving dynamics [43]. Achenbaum and Sterns [44] note there needs to be more agreement regarding when modernization first began as well as classifying stages within modernization.…”
Section: Psychosocial Theoriesmentioning
confidence: 99%
“…One may live in a highly modern society, yet demonstrate low levels of modernity or vice versa. Studying the relationship between ageism, modernization and modernity in six countries, these researchers found that modernization-but not modernity-was associated with negative attitudes towards older adults (Bengtson et al, 1975). Others employed qualitative or historical means to evaluate the relationship between attitudes towards older adults and modernization within a single country, reaching mixed conclusions about such a relationship (Chow & Bai, 2011;Rhoads, 1984).…”
Section: The Origins Of Ageismmentioning
confidence: 99%
“…Following a distinction between modernization and modernity, the present study evaluates both macro-and microlevel predictors of ageism using the modernization theory as a conceptual framework (Bengtson et al, 1975;Inglehart & Welzel, 2009 cross-national survey, such as the European Social Survey, the present study evaluates both macrolevel predictors that vary across cultures and societies and microlevel predictors that vary across individuals. The study is an attempt to explain variations in the occurrence of explicit negative and positive feelings towards older (individuals over 70) vs. younger (individuals in their 20s) adults.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that traditional values of filial piety have been eroded by the industrialization and urbanization of Asia in recent years (Bengtson & Smith 1968). An alternative explanation is that public avowals of filial piety belie private ascriptions to a negative view of aging and older adults (for related work, see Koyano 1989;McGee & Barker 1982).…”
Section: Introductionmentioning
confidence: 99%